PENERAPAN MODEL PEMBELAJARAN UNTUK MENINGKATAN LITERASI BACA TULIS: LITERATURE REVIEW - Raden Roro Endang Kusripinah; Heru Subrata (PIONIR: JURNAL PENDIDIKAN, 2022)
The low interest in reading students in Indonesia is also in line with the low interest in writing. Interest in reading and writing is actually the foundation for someone to be able to improve their literacy skills. Interest in reading and writing is actually a foundation for someone to be able to improve their literacy skills. The purpose of this research is to find out learning models that can be applied to improve literacy. This type of research uses qualitative research with library research methods (literature review). The library selection technique is based on the keyword learning model on literacy. The literature comes from research results obtained on the undergraduate google page with a publication limit of the last 15 years. The literature study technique used a synthetic matrix based on reference sources, sample types, methods, interventions, and findings. The conclusion was that the application of a learning model that could improve reading and writing literacy could be done using the learning method.